Pancreatic exocrine insufficiency in diabetes mellitus - M. V. Shestakova; I. V. Maev; A. S. Ametov; M. B. Antsiferov; D. S. Bordin; G. R. Galstyan; F. K. Dzgoeva; Y. A. Kucheryavyy; A. M. Mkrtumyan; T. V. Nikonova; E. Y. Pashkova (Сахарный диабет)
Diabetes is disease of both the endo- and exocrine parts of the pancreas. Pancreatic exocrine insufficiency (PEI) can occur in every 2–3 patients with diabetes and affect not only the quality, but also life expectancy. At the same time, the diagnosis and treatment of PEI is not getting enough attention. The endocrinologist, as the main specialist leading patients with diabetes, can diagnose and treat patients with pancreatic exocrine insufficiency and diabetes using adequate doses of pancreatic enzyme replacement therapy (PERT).